Three new species of Cheilolejeunea (Spruce) Steph. (Marchantiophyta, Lejeuneaceae) from northern Brazil - Bastos, Cid José Passos; Sierra, Adriel M.; Zartman, Charles E. (Phytotaxa, 2016)
Cheilolejeunea aracaensis sp. nov., Cheilolejeunea caracariense sp. nov., and Cheilolejeunea cuspidifera sp. nov. are described from Amazonas and Roraima states in northern Brazil. C. aracaensis differs from the other neotropical species in the genus by having the second and first lobule teeth elongated and paired, lacking subgynoecial innovations, a perianth with inflated ventral keels and inconspicuous rostrum. C. caracariensis is distinguished by its conical lobule, plane free margin, and a strongly papillose keel. C. cuspidifera is distinguished by being an irregularly dentate near the apex of the leaf lobe, second lobule tooth elongated and underleaves with cuspidate lobes.